Influence of electrospinning conditions on the characteristics of a nonwoven material based on fl uoroplast P(VDF-TFE) - Shabunina, Anna Yu.; Volokovoynova, Larisa D.; Kozhevnikov, Ilia O.; Zaitsev, Dmitrij P.; Terin, Denis V.; Saveleva, Мariia S.; Rusanova, Tatyana Yu.; Serdobintsev, Alexey A.; Demina, Polina A. (Известия Саратовского университета. Новая серия: Серия Химия. Биология. Экология)
Nonwovens produced through electrospinning technique have been successfully used in various fi elds due to their unique properties. It is essential to investigate the impact of the parameters in the manufacturing process on the resulting properties of these materials. This research focuses on nonwovens made from fl uoroplast P(VDF-TFE) using a horizontal spraying system with a vertically positioned collector. The parameters studied include the interelectrode distance, the electric fi eld strength, and the viscosity of the molding solution. The study aims to determine the optimal parameters for producing nonwovens with specifi c characteristics, such as size, fi ber diameter, and surface wettability. The results indicate that the interelectrode distance between 15 and 25 centimeters yields the best results. In this study, we have investigated the change in viscosity of the solution during the electrospinning process and have found that it should not exceed 5–7%. Additionally, we have observed changes in the structure of the polymer macromolecules, which depended on the rate of solvent evaporation during the fi ber stretching process. The results obtained in this research can be used to optimize the technological processes for industrial production of nonwoven fabrics made from fl uoroplast P(VDF-TFE) with specifi c properties.